Analisis Faktor-Faktor Kesulitan Belajar Bahasa Arab Siswa Kelas Vii Madrasah Tsanawiyah Nurul Hikmah Gantar Indramayu - Supanto, Supanto; Fanirin, Moch Hasyim; Arifin, Moh Mas'ud (JUPE : Jurnal Pendidikan Mandala, 2023)
Based on observations in several Madrasah Ibtidaiayah and Madrasah Tsanawiyah neighborhoods in the areas of Mekarsari, Haukolot and Gantar, many students when asked Arabic they looked embarrassed and could not answer from this problem which motivated the author to raise the title related to "Analysis of the Factors of Difficulty in Learning Arabic Students class VII at Madrasah Tsanawiyah Nurul Hikmah Gantar. Indramayu". The purpose of this study 1) To find out what factors are the difficulties in learning Arabic for the seventhgrade students of Madrasah Tsanawiyah Nurul Hikmah Gantar Indramayu 2) To find out what affect the difficulties in learning Arabic for the seventh grade students of Madrasah Tsanawiyah Nurul Hikmah Gantar Indramayu. This research method uses qualitative descriptive by using a naturalistic qualitative approach. The object of this research is Arabic teacher and seventh grade student of Madrasah Tsanawiyah Nurul Hikmah Gantar. The data sources of this research use primary data and secondary data. Data collection procedures use observation, interviews and documentation. Based on the results of the study, the factors of difficulty in learning Arabic at MTs Nurul Hikmah Gantar can be concluded that the factors that cause students difficulties in learning Arabic include 1) lack of interest and motivation from within students to learn Arabic, second, namely the difficulty of students reading and understanding the meaning of Arabic. of every Arabic vocabulary, third is parental attention to students about awareness and encouragement to learn outside school, fourth is the teacher's delivery method which is too monotonous, that is, only uses the lecture method and the use of learning media only uses books so that students feel not interested in learning. Arabic 2) influence the difficulty of learning Arabic for students of grade VII Madrasah Tsanawiyah Nurul Hikmah Gantar Indramyu internal students, school environment factors and family and community environments.